PSXI-31 How is the ingestive behaviour of mid lactating Holstein cows grazing a fescue based pasture under two different defoliation intensities?. (5th December 2019) - Hinz, Oliver Fast; Chilibroste, Pablo; Menegazzi, Gabriel; Oborsky, Matías; Genro, Cristina; Soca, Pablo; Mattiauda, Diego A
Abstract: An experiment was performed to study the effect of two contrasting defoliation intensities of a fescue based pasture on the ingestive behaviour. Treatments were two grazing intensities: lax treatment (TL) 12 cm and control treatment (TC) 6 cm, with four replicants of 0.3 ha each. The starting of the experiment was determined by the three leaf stage. Twenty-four mid lactating Holstein cows were blocked according to parity, body weight, body condition score and calving date. Each plot was grazed by three cows during as many days as necessary until the defoliation height of each treatment was achieved (TL: 6 d; TC: 8 d). The pasture mass was 2530 ± 180 kgDM/ha and animals had access from 8:00 to 16:00. Each cow received 7.4 kgDM of supplementation (17% Crude Protein; 2.81 Mcal/kgDM). After PM milking (17:00 h) animals remained separated in 8 pens, where they received 5.5 kgDM in individual troughs. The remaining supplement was provided in the AM milking (05:00 h). During the access to the pasture, grazing and ruminating times and bites rate (BT; bites/minute) were determined every 5 minutes by visual observation at the beginning, middle and end of the experiment. Daily ruminating (DR) was also logged by electronic recorders in 2h periods (Heatime®HR, SCR Dairy). The PROC GLIMMIX of SAS (SAS 9.2, 2010) with a binomial response distribution and with Logit as a link function, was used to determine the probability of the different events. DR and BR were analysed with a mixed model with block and treatment as fixed effects. The probability of cows grazing was greater for TC than TL and lower for ruminating and DR (Table 1). There was no effect of treatment on BR (55 ± 8.8 bites/min). The changes observed on ingestive behaviour were reflected on productive performance (companion abstract).